Dampak Tradisi Ampiran terhadap Partisipasi Belajar Anak Usia Dini di Hari Efektif Belajar di Kecamatan Kejajar Wonosobo - Akhirina Putri Damayanti; Bambang Sugiyanto; Robingun Suyud El Syam (YASIN, 2026)
Local traditions play an important role in early childhood education because they can shape children’s social values, cultural identity, and learning experiences. However, studies that specifically discuss the impact of the Ampiran tradition on early childhood learning participation on effective learning days remain limited. This study aims to analyze the impact of the Ampiran tradition on early childhood learning participation on effective learning days in Kejajar Subdistrict, Wonosobo. This study used a descriptive qualitative approach with a field research design, involving three early childhood education institutions, namely PAUD Al-Amin, PAUD Mutiara Hati, and TK NU Kejajar, which were selected using purposive sampling. Data were collected through observation, semi-structured interviews, and documentation, then analyzed using the Miles and Huberman model. The results showed that the Ampiran tradition has a dual impact. On the one hand, this tradition fosters social values such as mutual cooperation, empathy, and the strengthening of cultural identity. On the other hand, when its implementation takes place on or close to effective learning days, this tradition affects the decline in children’s attendance, concentration, and learning participation due to fatigue from activities that continue until nighttime. These findings contribute to the development of Vygotsky’s sociocultural theory in the context of local culture-based early childhood education in Indonesia. The conclusion of this study emphasizes the importance of balancing cultural preservation and the fulfillment of early childhood learning rights. The implications of this study provide theoretical contributions to the development of the literature on culture-based early childhood education as well as practical contributions for teachers, parents, and policymakers in integrating local traditions into the Kurikulum Merdeka framework in a more adaptive and child-friendly manner.